2007
DOI: 10.1111/j.1748-1716.2006.01650.x
|View full text |Cite
|
Sign up to set email alerts
|

Skilled digit movements in feline and primate – recovery after selective spinal cord lesions

Abstract: Recovery of voluntary movements after partial spinal cord injury depends, in part, on a take-over of function via unlesioned pathways. Using precise forelimb movements in the cat as model, spinal pathways contributing to motor restitution have been investigated in more detail. The food-taking movement by which the cat graSPS a morsel of food with the digits and brings it to the mouth is governed by interneurones in the forelimb segments (C6-Th1) and is normally controlled via the cortico- and rubrospinal tract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
41
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 56 publications
1
41
0
1
Order By: Relevance
“…BDA ϩve axons were seen extensively at 1.5 mm rostral to lesion (k); however, fewer were seen at 0.5 mm rostral to the lesion (l) and at the lesion site (m). Scale bar, 200 m. (Whishaw et al, 1993(Whishaw et al, , 1998Basso et al, 1996;McKenna and Whishaw, 1999;Starkey et al, 2005;Pettersson et al, 2007). After injury, animals recover most gross motor functions rapidly, but show a sustained deficit in skilled paw reaching (Bradbury et al, 2002;García-Alías et al, 2008.…”
Section: Discussionmentioning
confidence: 99%
“…BDA ϩve axons were seen extensively at 1.5 mm rostral to lesion (k); however, fewer were seen at 0.5 mm rostral to the lesion (l) and at the lesion site (m). Scale bar, 200 m. (Whishaw et al, 1993(Whishaw et al, , 1998Basso et al, 1996;McKenna and Whishaw, 1999;Starkey et al, 2005;Pettersson et al, 2007). After injury, animals recover most gross motor functions rapidly, but show a sustained deficit in skilled paw reaching (Bradbury et al, 2002;García-Alías et al, 2008.…”
Section: Discussionmentioning
confidence: 99%
“…Thus we distinguish two pontine reticulospinal pathways to spinal MNs, one uncrossed and the other crossed, of which the uncrossed pathway transmits more faithfully and appears to be more direct. motor control; descending pathways; brain stem; spinal cord; trunk; limb THE MAMMALIAN RETICULOSPINAL system, consisting of the mesencephalic, pontine, and medullary reticulospinal pathways, is crucial for the control of skeletal musculature (Baker 2011;Kuypers 1964;Lemon 2008;Perreault and Glover 2013;Peterson 1979;Pettersson et al 2007), but the neural mechanisms by which it initiates and regulates movement are far from understood.Electrical stimulation has been a key method in studying the organization of the mammalian reticulospinal system, revealing excitatory reticulospinal connections (mono-and polysynaptic) with axial motoneurons (MNs), proximal and distal limb MNs, and digit MNs in a variety of species (monkey: Davidson and Buford 2006;Riddle et al 2009; cat: Drew and Rossignol 1990b;Galea et al 2010;Grillner et al 1968;Jankowska et al 2003;Lloyd 1941;Peterson et al 1979;Sprague and Chambers 1954;Wilson and Yoshida 1969; rat: Bolzoni et al 2013; Floeter and Lev-Tov 1993;Umeda et al 2010; and mouse: Alstermark and Ogawa 2004;Szokol et al 2008). However, many studies have not differentiated among different areas of the reticular formation (RF) that project to the spinal cord.…”
mentioning
confidence: 99%
“…Thus we distinguish two pontine reticulospinal pathways to spinal MNs, one uncrossed and the other crossed, of which the uncrossed pathway transmits more faithfully and appears to be more direct. motor control; descending pathways; brain stem; spinal cord; trunk; limb THE MAMMALIAN RETICULOSPINAL system, consisting of the mesencephalic, pontine, and medullary reticulospinal pathways, is crucial for the control of skeletal musculature (Baker 2011;Kuypers 1964;Lemon 2008;Perreault and Glover 2013;Peterson 1979;Pettersson et al 2007), but the neural mechanisms by which it initiates and regulates movement are far from understood.…”
mentioning
confidence: 99%
“…It must be emphasized, however, that the single damage of the CPPS is not expected to produce permanent locomotor impairments, because the takeover of foreleg motor function by other tracts is common after selective cervical spinal cord lesions. 17,32,79 Hence, the permanent deficits were very likely caused by damage of brain descending axons together with damage of axons of the CPPS.…”
Section: Axonal Tracts Involved In the Production Of Permanent Motor mentioning
confidence: 99%
“…10 The loss and recovery of forelimb motor function has been studied in several models of cervical SCI in rats, 4,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] cats, [28][29][30] and primates. [31][32][33][34][35] All those studies demonstrated some extent of spontaneous motor function recovery, albeit with persisting deficits as a consequence of interruption of descending axonal tracts or segmental neuronal death. Despite these advances, there is still a need of cervical SCI models in which motor performance is comprehensively assessed in the long term to determine the motor components that show recovery and to link the chronic deficits with the neuroanatomical damage.…”
Section: Introductionmentioning
confidence: 99%